The Effectivity of IC50 Test between Green Tea and Curcumin Extracts from Mt. Lawu as an Antioxidant for SOD and MDA Levels in a Cisplatin Rat Model - Primadewi, Novi; Kariosentono, Harijono; Probandari, Ari; Wiboworini, Budiyanti (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract Purpose: This study aims to determine the relationship of the effective dose between Mt. Lawu green tea and Mt. Lawu curcumin as antioxidants based on superoxide dismutase (SOD) and malondialdehyde (MDA) levels. Methods: Blood was undertaken through the orbital sinus and allowed to stand until serum was formed. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) method was used to observe the effective dose of Mt. Lawu green tea and curcumin by quantifying the color change of each sample after incubation. The color change measured the absorbance value through a spectrophotometer. The data were analyzed using a correlation test to measure the effective concentration of Mt. Lawu green tea and Mt. Lawu curcumin toward SOD and MDA as antioxidant parameters in a cisplatin (CN) rat model. Result: The study results show that the IC50 green tea concentration of 0.75 ± 0.16 µg/mL and the curcumin concentration of 5.3 ± 0.4 µg/mL can reduce 50% of DPPH. Based on the graphs, SOD increased and MDA decreased. Discussion and Conclusion: This study demonstrates that the IC50 parameter of Mt. Lawu green tea and curcumin extracts is a good indicator for assigning the SOD and MDA levels in a CN rat model. Extracts derived from Mt. Lawu green tea and curcumin have ideal lowering DPPH, and the dosage has a strong relationship with the increase in SOD and the decrease in MDA.